Effect of urea applied in soil and by foliar sprayng on yeld and quality of wheat (Triticum aestivum, L.) - Néptune, A.M.L.; Lourenço, R.S. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1977)
The objective of the present work was to study the effect of nitrogen fertilizers on wheat (Triticum aestivum L.), under field conditions. The experiments were carried out in 1971 at the Vila Velha Experimental Station of the Agricultural Office of the State of Paraná, situated in the urban district of Ponta Grossa-PR. Treatments with 60 and 90 Kg N/ha and without nitrogen were compared, in the presence of 120 Kg P2O5/ha, in the form of superphosphate and 60 Kg K2Ο/ha in the form of potassium chloride. The nitrogen fertilizer used was urea, with 45% of nitrogen, applied in solid form in the planting furrow and as a top dressing, and in both the solid form and as a 2% solution sprayed onto the leaves at the tillering and booting stages. The results obtained showed that an increase in grain production occurred when nitrogen was applied, although there was no significant difference between time of application, split application, form and quantity of nitrogen. Production of protein, as measured by total nitrogen, was significantly higher for doses of 90 kgN/ha. As far as the use of fertilizer in the solid form is concerned best results were obtained with split application or with applications at later stages. This was not true, however, when application was made by sprayng the leaves. The forms of application were equivalent. Nitrogen application decreases the level of lysine and increases the gluten content content of the grain, when compared with the control.